Implementation of the Hamming Code for the Detection and Correction of Errors in a Telerobotic System Using an Industrial Communication Protocol - Urrea-Onate, E (Institute of Electrical and Electronics Engineers Inc., 2020)
Data transmission at the industry level encounters problems due to different factors such as noise and electromagnetic interference. This project presents an application for the control of a 3-DOF fault-tolerant robot through the implementation of an encoder and a Hamming decoder (7.4). Data transmission is conducted using a wireless system with XBee modules, while the Modbus RTU Master-Slave industrial communication protocol is employed for communication with the manipulator robot.To implement the master, a PC where the Hamming encoder responsible for placing the redundancy bits is installed, and an Xbee module for sending the information through the Modbus protocol are used. For the slave, a second Xbee module and a pcDuino board are used, where the Hamming decoder is located - which is responsible for receiving the encoder s information and perform the detection and correction of errors of the data sent by the master - to then be sent to the Expander Pi board, where the respective PWMs that manage the movement of the manipulator robot are located. © 2020 IEEE.